2023
DOI: 10.1021/acscatal.3c02618
|View full text |Cite
|
Sign up to set email alerts
|

Counting Sites in Lewis Acid Zeolite Sn-Beta: Connecting Site Quantification Experiments and Spectroscopy To Investigate the Catalytic Activity for the Alcohol Ring Opening of Epoxides

Abstract: Sn-Beta is a promising catalyst for numerous reactions involved in biomass upgrading and fine chemical production, but it is complex with multiple types of active sites. The activity for Sn-Beta can be calculated on a per-site basis using site quantification experiments that involve adding a Lewis basic probe molecule, but it is not clear which types of sites are being titrated. Our work connects site quantification experiments with spectroscopic measurements to explain differences in the catalytic activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…It has been reported that closed (Sn–(OSi) 4 ), hydrolyzed-open ((HO)–Sn–(OSi) 3 )⋯HO–Si), and defect-open ((HO)–Sn–(OSi) 3 ) Sn sites exist on SnBeta materials which could be quantified by varied approaches. 24,26,27 Based on the CD 3 CN-DRIFTS results (Fig. S4†), we postulate that both defect open and closed Sn sites exist on the SnBeta synthesized by liquid-phase grafting method.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…It has been reported that closed (Sn–(OSi) 4 ), hydrolyzed-open ((HO)–Sn–(OSi) 3 )⋯HO–Si), and defect-open ((HO)–Sn–(OSi) 3 ) Sn sites exist on SnBeta materials which could be quantified by varied approaches. 24,26,27 Based on the CD 3 CN-DRIFTS results (Fig. S4†), we postulate that both defect open and closed Sn sites exist on the SnBeta synthesized by liquid-phase grafting method.…”
mentioning
confidence: 88%
“…To unravel the site requirements of this reaction on the obtained materials, the chemical and physical properties of conned dual Lewis acidic Ce and Sn centers were examined using XRD, 1 H-SSNMR, diffuse reectance (DR) UV-Vis (Ultraviolet-Visible Spectroscopy), and Diffuse Reectance Infrared Fourier Transform Spectroscopy (DRIFTS)-pyridine. By employing a well-established dealumination procedure, 14 framework Al species were extensively removed to yield Beta-deAl with a Si/Al = 600, as conrmed by 27 Al-solid state nuclear magnetic resonance (SSNMR) and inductively coupled plasma (ICP) analysis (Fig. S2 and Table S2 †, respectively).…”
mentioning
confidence: 99%
“…They attributed the rate increases to a decrease in the density of (SiOH) x groups that leads to entropic gains for ring-opening. More recent work used site quantification, rate measurements, and 15 N NMR of adsorbed pyridine to show that Sn sites adjacent to (SiOH) x nests provide greater turnover rates for epoxide ring-opening than Sn sites adjacent to a point SiOH defect . These findings indicate that the (SiOH) x structure near Sn atoms influences ring-opening kinetics, which may stem from differences in local solvent structure.…”
Section: Introductionmentioning
confidence: 99%
“…, closed or open sites), and display different acidities, which all together will influence the catalytic performance. 34,35 Moreover, different synthesis methods may lead to different pore structures, crystallite sizes, and concentrations of defect sites (which determines the hydrophobicity or hydrophobicity), which will also affect the catalytic performance. 36–39 Significant advances in the qualification and quantification of the location, fine structure and acidity of heteroatom centers confined in zeolites have also been made in recent years.…”
Section: Introductionmentioning
confidence: 99%